Constipation and herbal medicine - Iizuka, Norio; Hamamoto, Yoshihiko (Frontiers in Pharmacology, 2015)
Constipation is characterized by a variety of bowel symptoms such as difficulty passing stool, hard stool, and a feeling of incomplete evacuation. The multifactorial causes of constipation limit the clinical efficacy of current conventional treatments that use a single drug that acts through only one pathway. To complement the shortcomings of the current Western medical model and provide a complete holistic approach, herbal medicines capable of targeting multiple organs and cellular sites may be used. In Japan, many herbs and herbal combinations have traditionally been used as foods and medicines. Currently, Japanese physicians use standardized herbal combinations that provide consistent and essential quality and quantity. This review highlights representative Japanese herbal medicines (JHMs), Rhei rhizoma-based JHMs including Daiokanzoto and Mashiningan, and Kenchuto-based JHMs including Keishikashakuyakuto and Daikenchuto, which coordinate the motility of the alimentary tract. This review provides a framework to better understand the clinical and pharmacological efficacies of JHMs on constipation according to the unique theory of Japanese traditional medicine, known as Kampo medicine.